Brassinosteroid Regulates Cell Elongation by Modulating Gibberellin Metabolism in Rice . Issue 11 (4th November 2014) - Tong, Hongning; Xiao, Yunhua; Liu, Dapu; Gao, Shaopei; Liu, Linchuan; Yin, Yanhai; Jin, Yun; Qian, Qian; Chu, Chengcai
Abstract : Physiological BR promotes cell elongation by inducing GA accumulation through activation of GA3ox-2 expression, whereas exogenously applied high concentrations of BR inhibit cell elongation by repressing GA level. As a feedback mechanism, GA extensively inhibits BR biosynthesis and signaling. Abstract: Brassinosteroid (BR ) and gibberellin (GA ) are two predominant hormones regulating plant cell elongation. A defect in either of these leads to reduced plant growth and dwarfism. However, their relationship remains unknown in rice ( Oryza sativa ). Here, we demonstrated that BR regulates cell elongation by modulating GA metabolism in rice. Under physiological conditions, BR promotes GA accumulation by regulating the expression of GA metabolic genes to stimulate cell elongation. BR greatly induces the expression of D18 / GA3ox-2, one of the GA biosynthetic genes, leading to increased GA1 levels, the bioactive GA in rice seedlings. Consequently, both d18 and loss-of-function GA -signaling mutants have decreased BR sensitivity. When excessive active BR is applied, the hormone mostly induces GA inactivation through upregulation of the GA inactivation gene GA2ox-3 and also represses BR biosynthesis, resulting in decreased hormone levels and growth inhibition. As a feedback mechanism, GA extensively inhibits BR biosynthesis and the BR response. GA treatment decreases the enlarged leaf angles in plants with enhanced BR biosynthesis or signaling. Our results revealed a previously unknown mechanism underlying BR and GA crosstalk depending on tissues and hormone levels, which greatly advances our understanding of hormone actions in crop plants and appears much different from that in Arabidopsis thaliana .